Uterine tumor resembling ovarian sex cord tumor: A case report - Girishma Shrestha; Rohit Khadgi (Association of Clinical Pathologists of Nepal, 2023)
Uterine tumor resembling ovarian sex cord tumor (UTROSCT) is a rare uterine neoplasm of uncertain histogenesis, with presence of ovarian sex cord-like elements. These tumours typically occur in perimenopausal and postmenopausal women, and are considered to behave in an indolent fashion in most of the cases. However, recurrences and metastases have also been reported. We report a case of a 37 year old female who presented with lower abdominal pain and abnormal uterine bleeding, and underwent hysterectomy following a clinical and radiological suspicion of a submucosal uterine fibroid. Macroscopically the tumor resembled a Leiomyoma. However, the diagnosis of UTROSCT was made after histopathological examination and immunohistochemical studies. Clinicians and pathologists need to be aware of this diagnosis, given the rarity of this condition and potential aggressive clinical course.